Wound bed preparation: TIME for an update. (September 2016) - Harries, Rhiannon L; Bosanquet, David C; Harding, Keith G
Abstract: While the overwhelming majority of wounds heal rapidly, a significant proportion fail to progress through the wound‐healing process. These resultant chronic wounds cause considerable morbidity and are costly to treat. Wound bed preparation, summarised by the TIME (Tissue, Inflammation/infection, Moisture imbalance, Epithelial edge advancement) concept, is a systematic approach for assessing chronic wounds. Each of these components needs to be addressed and optimised to improve the chances of successful wound closure. We present an up‐to‐date literature review of the most important recent aspects of wound bed preparation. While there are many novel therapies that are available to the treating clinician, often, there are limited data on which to assess their clinical value, and a lack of appreciation for adequate wound bed preparation needed before expensive therapy is used to heal a wound.